STUDY OF THE EFFICIENCY OF NATURAL ANTIOXIDANTS IN STORING POULTRY RAW MATERIAL PROCESSING - Kuzmina Nadezhda Nikolayevna; Petrov Oleg Yuryevich; Semenov Vladimir Grigorievich; Baimukanov Dastanbek Asylbekovich; Lyubimov Alexander Ivanovich; Aubakirov Khamit Abilgazievich (Scientific Journal of Pedagogy and Economics, 2020)
. The efficiency of using dihydroquercetin as an antioxidant, which increases the duration of storage of poultry processing raw materials, is investigated. A comparative assessment of the effectiveness of the natural antioxidants of vitamins E, C, rutin, and dihydroquercetin was carried out for the duration of storage of minced meat from the fillet, meat of deboned meat and skin from broiler carcasses. The introduction of antioxidants in the experimental samples of raw materials ensured, during 28 days of storage, a lower value of the indicators of oxidative spoilage: the acid number by an average of 74%, and the peroxide number by 1.5-1.7 times, relative to these indicators in the control sample antioxidants. The use of dihydroquercetin in experimental samples of frozen mechanically deboned meat for long-term storage, in the studied concentrations, ensured after 1 month of storage a lower value of the oxidative spoilage indicators: the acid number was 2–10% lower, and the peroxide number was 1.5 and 1.7 times lower, relative to these indicators in the control sample. The results confirm the high efficiency of the use of dihydroquercetin as an active antioxidant, which makes it possible to use it along with existing analogues.